A qualitative exploration of school-based staff's experiences of delivering an alcohol screening and brief intervention in the high school setting: findings from the SIPS JR-HIGH trial. (29th October 2018) - McGeechan, G J; Giles, E L; Scott, S; McGovern, R; Boniface, S; Ramsay, A; Sumnall, H; Newbury-Birch, D; Kaner, E; ,
Abstract: Background: Whilst underage drinking in the UK has been declining in recent years, prevalence is still higher than in most other Western European countries. Therefore, it is important to deliver effective interventions to reduce risk of harm. Methods: Semi-structured interviews with staff delivering an alcohol screening and brief intervention in the high-school setting. The analysis was informed by normalization process theory (NPT), interviews were open coded and then a framework applied based on the four components of NPT. Results: Five major themes emerged from the analysis. The majority of participants felt that the intervention could be useful, and that learning mentors were ideally suited to deliver it. However, there was a feeling that the intervention should have been targeted at young people who drink the most. Conclusions: The intervention was generally well received in schools and seen as an effective tool for engaging young people in a discussion around alcohol. However, in the future schools need to consider the level of staffing in place to deliver the intervention. Furthermore, the intervention could focus more on the long-term risks of initiating alcohol consumption at a young age.